Income-Generating Effects of a Balanced Budget - Wallich, Henry C. (Quarterly Journal of Economics, 1944)
Scope of the paper: effects of a non-progressive balanced increase in the budget, 78. — The mechanics, 79. — Qualifications: character of government output, 82; competition with private enterprise, 83; effect upon the propensity to consume, 83; further effects of taxation, 85. — Comparison of income-generating measures, 88.